Functionalized calcium carbonate microparticles in ethyl cellulose films: A vehicle for sustained amoxicillin release for medical applications - Petru Niga; Simone Sala; Jenny Rissler; Lina Nyström; Anna Fureby; Ulla Elofsson; Joachim Schoelkopf; Roger Roth; Patrick Gane (PLoS ONE, 2026)
The continuous quest for materials capable of providing sustained release of antimicrobial drugs is particularly important for indwelling medical applications. In this study, we utilized amoxicillin as a model active pharmaceutical ingredient (API) to investigate the feasibility of using porous media – specifically, functionalized calcium carbonate (FCC) microparticles – as a primary drug carrier embedded within an ethyl cellulose (EC) polymer film. Our main objective was to prolong and sustain the release of the API. The fabrication process of the microparticle containing film involved two key steps: loading the model API into the FCC particles and then embedding these loaded particles into the polymeric film. Amoxicillin was loaded into the FCC particles using a solvent evaporation method. Detailed characterization through Scanning Electron Microscopy (SEM), lab- and synchrotron-based XRD revealed that amoxicillin precipitated both inside and on the surface of the FCC particles, predominantly in an amorphous form. Additionally, ultraviolet-visible (UV-vis) spectroscopic data demonstrated an increased release rate from the porous FCC compared to direct dissolution of pure amoxicillin powder. Embedding amoxicillin pre-loaded porous FCC particles in the EC film led to a more rational sustained release compared with powder amoxicillin embedded directly in the film, advantageously delivering the same amount of amoxicillin over a longer period; a result that may be relevant for indwelling medical devices such as urinary catheters, vascular access devices or wound drains.